Utilization manufactured sand as fine aggregate for concrete quality - Hidayawanti, Ranti; Legino, Supriadi; Sangadji, Iriansyah (International Journal of Engineering and Technology, 2018)
Utilization Manufactured sand (M-sand) in this case of ash sandstone wash as a substitute for sand on concrete mixture is used as a result of the crisis in availability of the main material of concrete, ie natural materials such as sand used in concrete manufacture foundries. M-sand from the production of crushed stone then collected and washed which will be used as a mixture of sand on the concrete. The results of m-sand optimally utilized for the mixture of fine agregate substitution of concrete with compressive strength test to produce high quality of concrete. The mixture used is 50% m-sand and FA, from the results of the compressive strength test showed the utilization of m-sand can be used as a quality concreteÂ Â